Basal and Regulatory Promoter Studies of the AKR1C3 Gene in Relation to Prostate Cancer - Schulze, Jenny J.; Karypidis, Helena; Ekström, Lena (Frontiers in Pharmacology, 2012)
Background: Human 17-hydroxysteroid dehydrogenase type 5 (17-HSD5) formally known as aldo-keto reductase 1C3 (AKR1C3) play a major role in the formation and metabolism of androgens. The enzyme is highly expressed in the prostate gland and previous studies indicate that genetic variation in the AKR1C3 gene may influence the prostate volume and risk of prostate cancer. Aim: Here we aimed to further study the genetic regulation of AKR1C3 and its putative role in prostate cancer. Experiments: A previously identified promoter polymorphism (AG, rs3763676) localized at –138 from the translational start site were studied in relation to prostate cancer in a Swedish population-based case control study including 176 patients diagnosed with prostate cancer and 161 controls. Moreover, we have studied the basal and androgen induced promoter activity of the AKR1C3 gene. Expression studies with AKR1C3 promoter reporter constructs were performed in HepG2 and DSL2 cells. Results: We found that carriers of the promoter A-allele had a borderline significant decreased risk of prostate cancer (OR=0.59; 95% CI=0.32-1.08). We also show that dihydroteststosterone (DHT) induced the promoter activity of the A-allele 2.2 fold (p=0.048). Sp3 seem to play an important role in regulating the transcription activity of AKR1C3 and site-directed mutagenesis of a GC-box 78 base-pair upstream the ATG-site significantly inhibited the basal AKR1C3 promoter activity by 70%. Conclusion: These results further supports previous findings that the AG promoter polymorphism may be functional and that AKR1C3 plays a critical role in prostate carcinogenesis. Our findings also show that the members of Sp family of transcription factors are important for the constitutive expression of AKR1C3 gene.